An overview of changes in the program course of applied mathematics at KUT - Pekarskas, Vidmantas Povilas (Lietuvos matematikos rinkinys, 2010)
The paper gives an overview on when and how the program of the Applied Mathematics studies course has been changing during the years. The list of mathematics courses read during different years in this studies program is presented. These time intervals are marked by 1964, 1969, 1974, 1983, 1993 as the studies program of Applied Mathematics was experiencing changes then. The amount of mathematical subjects measured in hours is compared for each time interval.
Keywords: applied mathematics; mathematics courses